Mesalazina: profilo farmacologico, terapeutico e farmacoeconomico - Eandi, Mario; Ferrero, Laura (Farmeconomia. Health economics and therapeutic pathways, 2003)
The term inflammatory bowel diseases (IBD) refers to two distinct clinical entities: Crohn.s disease and ulcerative cholitis, two chronic and non-specific disorders of unknown origin. Although quite uncommon and usually not life-threatening, IBDs have a strong economical impact, as they tend to affect patients in high productivity ages and require long and demanding therapies, medical and sometimes surgical. The pharmacological approaches to IBD treatment include aminosalicylates, corticosteroids and immunosuppressive agents. Aminosalicylic acids are the most widely used agents for maintaining remission and for the cure of mild-tomoderate forms of IBDs. This paper outlines the main pharmacological and clinical properties of one of these drugs, mesalamine (mesalazine). Mesalamine is the active moiety of sulfasalazine, an effective but not always tolerated agent. Mesalamine is available in several pharmaceutical forms, to be administered either by the oral or by the rectal route. As the therapeutic action of aminosalicylates is ascribed to their topical action on the inflamed intestine, while the adverse effects are believed to be caused by the systemically adsorbed (mainly in the first tract of the small bowel) fraction, slow-release formulations are usually preferred. From an economical point of view, mesalamine appears to have a moderate acquisition cost, widely offset by the savings induced on direct sanitary and, most importantly, indirect costs of IBDs. In particular, the availability of a generic drug with advanced colon-delivery technology provides the physician with the opportunity to treat patients with the best available technology at a reasonable price.